The Territorialisation of Social Inclusion Policies from the Perspective of the Spanish Rural Areas: Regional Comparative - Escribano-Pizarro, Jaime; Serrano-Lara, José Javier; Valero-López, Diana Esmeralda (Revista de Estudios Andaluces, 2020)
This article explores how the attention to rural areas is materialised in the plans for social inclusion in Spain. We analyse the national and autonomous frameworks classifying the Autonomous Communities (AACC) according to their degree of rurality (OCDE). Therefore, we establish if there is a relationship between the territorial character of each AACC and the type of inclusive actions set for rural areas, and which are the topics approached. The results show that the predominantly rural autonomous communities do not register the most substantial quantity of actions targeted to rural areas and that the themes more developed are on planning and regional development, education and training enhanc.